IMPLEMENTASI MERDEKA BELAJAR DALAM MENINGKATKAN MUTU PENDIDIKAN NONFORMAL PADA DAERAH TERTINGGAL - Aulia Rusnaini Hasibuan; Ariana Ariana; Nadia Partiwi; Nomy Anggraini (Universitas Negeri Medan, 2022)
This study aims to determine how the implementation of independent learning in improving the quality of non-formal education in disadvantaged areas. Research conducted using Where in this case, researchers conducted research using descriptive research and using a qualitative approach. The data collection technique used in this research is literature study (literature study). Literature study is a form of research conducted through searches by reading various sources including books, journals, and other publications related to the topic, issue or problem at hand.